2009
DOI: 10.1007/s00428-009-0778-y
|View full text |Cite
|
Sign up to set email alerts
|

Gross genomic alterations differ between serous borderline tumors and serous adenocarcinomas—an image cytometric DNA ploidy analysis of 307 cases with histogenetic implications

Abstract: Our objective was to study the gross genomic alterations in serous borderline tumors and serous adenocarcinomas of the ovary. A retrospective analysis of 245 serous borderline tumors and 62 serous adenocarcinomas from 249 patients was performed using high-resolution image cytometric DNA ploidy analysis. DNA ploidy status, S-phase fraction, and DNA index were evaluated. The majority of serous borderline tumors were diploid (225/245 cases, 92%). The remaining 8% showed an aneuploid peak predominantly with DNA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(36 reference statements)
3
6
0
Order By: Relevance
“…These data are very similar to those described in the whole exome analysis of low grade serous carcinomas [9]. As might be expected, low grade serous invasive carcinomas have a DNA content and level of copy number alterations that more closely resembles SBTs than high grade serous tumors, but which are intermediate between the two [29,30]. In contrast, high grade serous carcinomas are generally aneuploid with a high level of copy number alterations [8,30] and data from the TCGA ovarian study indicate that these tumors typically sustain 50–70 somatic mutations, with TP53 representing a clear driver mutation in this tumor type [8].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These data are very similar to those described in the whole exome analysis of low grade serous carcinomas [9]. As might be expected, low grade serous invasive carcinomas have a DNA content and level of copy number alterations that more closely resembles SBTs than high grade serous tumors, but which are intermediate between the two [29,30]. In contrast, high grade serous carcinomas are generally aneuploid with a high level of copy number alterations [8,30] and data from the TCGA ovarian study indicate that these tumors typically sustain 50–70 somatic mutations, with TP53 representing a clear driver mutation in this tumor type [8].…”
Section: Resultssupporting
confidence: 86%
“…With respect to chromosomal instability, SBTs are relatively genetically stable, in terms of both DNA ploidy [29] and copy number alterations [30], consistent with the low number of genetic mutations identified in this study. Only 10 somatic genetic mutations were identified in tumor SBT-s2, and seven in tumor SBT-s5.…”
Section: Resultssupporting
confidence: 79%
“…Alternatively, the absence of identifiable KRAS or BRAF mutations in benign serous tumors with clear clonal expansion events leaves open the possibility that they may be precursors for other serous ovarian cancers. The tetrasomy identified in the epithelial component in case A2, adjacent to fibroblasts with chromosome 12 trisomy, is a particularly intriguing finding in light of ploidy studies by Pradhan and colleagues that identified tetraploidy in 7 of 40 high-grade serous carcinomas, 0 of 22 LGSCs, and 0 of 245 SBTs (34).…”
Section: Discussionmentioning
confidence: 82%
“…These carcinomas have a DNA content and level of copy number alterations that closely resembles that of SBTs [24,25]. …”
Section: Ovarian Carcinoma Typesmentioning
confidence: 99%